(untitled) (Global Media Journal - German Edition, 2021)
This article reflects experiences and results from an environmental education and communication strategy (EECS) as part of a Lao-German development project of Gesellschaft für Internationale Zusammenarbeit (GIZ) over a 10-year period from 2011 to 2021. The article is divided into four parts. First, an overview of the project context and the media landscape in Laos is provided. Next, the conceptual framework of the communication strategy at the GIZ policy and project management level is presented. Subsequently, major features of the wide variety of environmental education and communication media productions and educational materials are highlighted. Another chapter summarizes the results of Knowledge, Attitude and Practice (KAP) surveys related to environmental awareness. Finally, monitoring and evaluation (M&E) and impact assessment results conclude lessons that can be learned from the project’s communication strategy.